Pengaruh Kualitas Pelayanan Terhadap Kepuasan Masyarakat Di Kantor Desa Suka Jadi Kecamatan Kuala Cenaku Tahun 2021 - Surya Akbar (JIAGANIS, 2021)
ABSTRACTThis research was conducted at the Suka Jadi Village office, Kuala Cenaku District. The purpose of this study was to determine the effect of service on community satisfaction in the office of Suka Jadi Village, Kuala Cenaku District. The types and sources of data used in this study are primary data, namely data obtained directly from respondents as visitors to the Desa Suka Jadi village office, Kuala Cenaku District. The number of samples determined was 30 respondents with the incidental sampling technique, namely the sampling technique based on chance, whoever became a visitor at the Desa Suka Jadi village office, Kuala Cenaku District and met the researcher directly and was willing to be a respondent would be used as the research sample. To be able to collect data in accordance with what is needed by the author, the authors use several techniques in data collection, namely observation, interviews and literature study. From the results of the research conducted by the author, it can be concluded that the results of simple regression analysis are obtained Y = -0.029 + 1.0 X, α = -0.029, meaning that if the quality of public services is equal to 0 (zero) then the amount of community satisfaction is -0.029 points, β = 1.0 means that if the Quality of Public Services increases by 1 (one) unit, the Community Satisfaction will increase by 1.0 points. T test results, sig value 0,000. The sig value is smaller than the probability value of 0.05, or the value of 0.000 <0.05, then H1 is accepted and Ho is rejected. Variable X has tcount, namely 114.233 with ttable = 2.052 So tcount> ttable can be concluded that variable X has a contribution to Y. A positive t value indicates that variable X has a unidirectional relationship with Y.So it can be concluded that service quality has a significant effect on community satisfaction.